Discourses about the meaning of the local food Investigations in Romanian urban contexts - Nistor, Laura (Socio.hu Társadalomtudományi Szemle, 2015)
Abstract Up to now only a few studies about local food consumption in Romania have been realized and the majority of them are quantitative investigations. The aim of the present research which is based on focus group interviews was to bring further nuance to these previous quantitative data by asking the respondents to develop deeper narratives about what local food means to them, how they relate to local foods, how they perceive the different features of local foods (e.g. tradition, organic, taste, ingredients, etc.) and which are their motivations and impediments in connection with local food consumption. The research showed that consumers’ involvement with local food occurs along product–based aspects, i.e. the intrinsic characteristics of food (taste, ingredients) and local food consumption seems to be much more motivated by health concerns and status assignment than by ethical and ecological reasons. Two major definitions of local food were mapped: 1) a place–centred, geographical definition and 2) a production–centred, ‘how it is made’ kind of definition. Keywords: local food, geographic narrative, tradition, identity